WhatsApp coup jokes and the dialogue on Zimbabwean politics - Hugh Mangeya; Cuthbeth Tagwirei (Taylor and Francis Group, 2023)
This article analyses the dialogue stemming from viral WhatsApp jokes on the Zimbabwean coup in November 2017. It argues that coup jokes have created an opportunity to discuss the nature of Zimbabwean politics since 2000. This dialogue, characterised by ambivalence, multiplicity, and open-endedness, provides insights on the political traits that have dominated Zimbabwe since 2000. These are rendered as politics of personality, chimurenga and partisanship. While the architects of the coup sought to create and propagate one narrative, later described as ‘restoring legacy’, coup jokes carried internal contradictions, doubts and conflicts which made possible an understanding of the coup narrative as inherently dialogic. Selected WhatsApp coup jokes, which circulated between 14 and 24 November 2017, were studied. Insights from Bakhtin's dialogism were applied to the study of jokes in order to illuminate their contradictions, dualities and openness, and how this enabled an understanding of the traits that have dominated Zimbabwean politics.